Perceived Economic Inequality Measures and Their Association with Objective Inequality and Redistributive Preferences - García Castro, Juan Diego (2022)
Perceptions of economic inequality (PEI) play a central role in people’s responses to inequality. We aim to examine the consistency between different PEI measures (income gaps, diagrammatic figures, experienced downward and upward disparities), their relationship with objective inequality, and their association with redistributive preferences. Using data from the International Social Survey Programme 2019 (N = 34,387, 22 countries), we performed multilevel regression analyses and found that PEI indicators were weakly and positively correlated, suggesting that they represent different dimensions of the same construct. Furthermore, objective inequality was not related to PEI measures. Finally, all PEI measures were positively associated with support for redistribution, except for experienced upward inequality. We discuss the multidimensional nature of PEI and its implications on redistributive preferences.